Description of Ultrasonographic Examination of Carotic Arteries in Stroke Infark Patients in Tarakan Hospital Jakarta in 2021 - Martua Rizal Situmorang; Susilo Susilo; Ghita Dea Fany Situmorang (Jurnal MedScientiae, 2022)
Stroke is one of the main non-communicable diseases in Indonesia. Stroke data in Indonesia shows a continuous increase, both in terms of incidence, disability, or death. Stroke is a syndrome consisting of signs and or symptoms of focal or global loss of function of the central nervous system that develops rapidly (within seconds or minutes). These symptoms last for more than 24 hours or cause death, originating from impaired cerebral blood flow and not caused by transient cerebral blood circulation disorders, brain tumors, secondary strokes due to trauma or infection. Based on the pathogenesis, stroke is divided into two, including infarct and hemorrhagic stroke. Stroke can be classified according to the etiology or the basis of the course of the disease. Stroke infarction has two risk factors, namely modifiable and non-modifiable. The risk of stroke can increase if you have an unhealthy lifestyle such as eating foods high in cholesterol and high in lipids, lack of exercise, and lack of physical activity. Atherosclerosis is a plaque on the walls of the arteries so that there will be a narrowing of the lumen of the blood vessels. Investigations that can be done with carotid Doppler ultrasound.